The effects of audit quality on the value relevance of other comprehensive incomes - Levinska Primavera; Taufik Hidayat (Universitas Hayam Wuruk Perbanas, 2015)
Stockholders claim deals with handling crucial role to investors while another ac-counting measurement has not yet been paid attention by the investors and analysts. Beside, another comprehensive income despite of its equal role to net income also re-quires a deep concern. This research uses financial industry data in Indonesia Capital Market for 2011-2012 under panel method and also cross-section method as the addi-tional analysis. This research assesses the effect of audit quality on value relevance of other comprehensive income regarding subjectivity embedded in other comprehensive income components. These components are determined through fair value aspects, which eventually lead to management discretion in measuring other comprehensive income components. Subjective components of other comprehensive incomes consist of foreign exchange translation (forex), revaluation in fixed assets (rev), minimum pension liability adjustment (pen), and available-for-sale securities adjustment (sec). The audit quality is believed as a mechanism which can increase the value relevance of subjective of other comprehensive income components. On the other hand, when as-sessing the value relevance of other comprehensive income components both indivi-dually and in aggregate, it is encouraged by inconsistency of previous research results.